1993
DOI: 10.3109/10408419309113530
|View full text |Cite
|
Sign up to set email alerts
|

Petroleum Spill Bioremediation in Marine Environments

Abstract: Bioremediation is a promising technology for responding to marine oil spills. A majority of molecules in crude oils and refined products are biodegradable, and they will eventually leave the environment as they are consumed by microbes. Bioremediation aims to stimulate the rate of this process. Successful bioremediation efforts have so far focused on applying fertilizers to aerobic oiled shorelines to at least partially relieve the nitrogen limitation of biodegradation by indigenous microorganisms. Nevertheles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
127
1
4

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(135 citation statements)
references
References 123 publications
3
127
1
4
Order By: Relevance
“…Lepo and Cripe (1999) in their own findings showed that biodegradation ofPAHs was preferential to that ofn-alkanes in crude oil when they used some bacteria (Nocardia globerula, Rhodococcus fascians, Pseudomonas saccharophila). These findings contradicted the earlier view that the n -alkanes were generally considered the most biodegradable compound class within crude oil (Leahy and Colwell, 1990;Atlas and Bartha, 1992;Prince, 1993). The possible application of biodegradation in Antarctic was reported by Vasileva-Tonkova and Gesheva (2004), who isolated 17 microbes from Antarctic soil and all of them showed a good biodegradative potential for hydrocarbons.…”
Section: Microbial J 1 (4): 139-148 2011contrasting
confidence: 56%
“…Lepo and Cripe (1999) in their own findings showed that biodegradation ofPAHs was preferential to that ofn-alkanes in crude oil when they used some bacteria (Nocardia globerula, Rhodococcus fascians, Pseudomonas saccharophila). These findings contradicted the earlier view that the n -alkanes were generally considered the most biodegradable compound class within crude oil (Leahy and Colwell, 1990;Atlas and Bartha, 1992;Prince, 1993). The possible application of biodegradation in Antarctic was reported by Vasileva-Tonkova and Gesheva (2004), who isolated 17 microbes from Antarctic soil and all of them showed a good biodegradative potential for hydrocarbons.…”
Section: Microbial J 1 (4): 139-148 2011contrasting
confidence: 56%
“…The bacteria isolated in this study have been reported by other workers (Ajisebutu and Alofe, 2004;Atlas and Cerniglia, 1995;Igbinosa et al, 2007;Jennings and Tanner, 2000;Okoh et al, 1999Okoh et al, , 2001Prince, 1993). The pseudomonads were predominantly isolated on the ELCO-BSM agar plates (5 out of 11 isolates).…”
Section: Discussionsupporting
confidence: 48%
“…The utilization abilities of fungi to different hydrocarbons showed significant differences (Elshafie et al, 2007). Prince (1993) reported that microorganisms show a distinct preference for some hydrocarbons over other. Cl was preferred and the other inorganic and/or organic nitrogen sources repressed the biodegradation activity.…”
Section: Discussionmentioning
confidence: 99%